Long-Term Observation of a Child with Foreign Body Aspiration Pneumonia and Reccurent Cardiac Arrest from an Incarcerated Mothers - Muhammad Reza Syahli; Asrawati Asrawati; Indra Ihsan; Fitrisia Amelin; Riki Alkamdani (Indonesian Journal of Global Health Research, 2026)
This study employed a longitudinal case study design aimed at describing the clinical course, respiratory recovery, nutritional status, developmental progress, and social dynamics of a child with aspiration pneumonia accompanied by cardiac arrest. The research subject was a one-year-old girl who experienced baked potato aspiration while living in a correctional facility with her mother. The patient received intensive treatment at Andalas University Hospital and was subsequently monitored for three consecutive semesters after discharge. Data collection was conducted through multiple sources to obtain comprehensive information. Clinical data during the acute phase were obtained through a review of the patient’s medical records, including physical examination findings, laboratory and radiological results, and records of medical interventions provided during hospitalization. Follow-up data were collected through direct clinical observation during routine control visits, focusing on respiratory recovery, nutritional status, and developmental progress. Child development was assessed using standardized developmental screening tools, namely the Denver Developmental Screening Test II (Denver II) and the Capute Scales (CAT-CLAMS). Additional contextual data were obtained through in-depth interviews with the child’s parents, correctional facility health workers, and healthcare providers at the referral hospital to understand the caregiving environment and health management after discharge. Home visits were also conducted after the mother returned from the correctional facility to evaluate the child’s living conditions, caregiving practices, and environmental factors that might influence recovery and development. Data analysis was carried out using a descriptive and thematic approach. Clinical and developmental data were analyzed longitudinally to identify patterns of recovery from the acute phase to the follow-up period across three semesters. The analysis also explored the interaction between medical factors (such as treatment response and clinical outcomes) and social factors (including caregiving environment and family support) in influencing the child’s recovery and development. All research procedures adhered to pediatric ethical principles, including maintaining the confidentiality of the patient’s identity and obtaining informed consent from the family for documentation and analysis of the case. This approach allows for a comprehensive understanding of the child’s recovery process, integrating both clinical and social perspectives.